PERANCANGAN DESAIN GRAFIS MEDIA PROMOSI WEBSITE PASAR PAPRINGAN BAGI KELUARGA URBAN DI INDONESIA - Steven Arden; R.A Dita Saraswati; Puspita Yuli Pradita (Serat Rupa: Journal of Design, 2019)
Papringan Market is located in Ngadiprono Hamlet, Ngadimulyo Village, Kedu District, Temanggung, and Central Java. The Papringan market has a big idea to build a village from the village by revitalizing it. The Papringan market has good potential for tourist areas, because it has a unique transaction method, this market uses "pring" coins for trading. In addition, the creation of this market also changes the public order from the unused or the disposal of wasteland into a useful land. The design goal is to promote the Papringan Market to be better known by urban families in Indonesia.The research method used is Field observation, interviews with Papringan Market activists, and target markets research with quantitative methods through online questionnaires on 100 respondents. The main media used are Website and Video. The visuals raised the traditional elements such as bamboo, unique elements of space, and typical activities in the area that are not owned by other traditional markets. This promotion uses websites as the main media, because it is interactive, attractive, global reach, and up-to-date information. The results of this design are expected the Papringan Market opportunity more visible to residents in other big cities and able to reach urbanites in other cities, which are in fact traditional tourism activists.